Ph-Controlled Assembly of 3d and 2d Zinc-Based Metal-Organic Frameworks with Tetrazole Ligands - Venegas-Yazigi, D; Venegas-Yazigi, D; Herrera-Urbina, F; Canon-Mancisidor, W; Canon-Mancisidor, W; Singh, D; Enríquez-Montenegro, J; Manquián-Villalobos, C; Chi-Duran, I (American Chemical Society, 2018)
We report the synthesis and structural diversity of Zn(II) metal-organic framework (MOF) with in situ formation of tetrazole ligand 3-ptz [3-ptz = 5-(3-pyridyl)tetrazolate] as a function pH. By varying the initial reaction pH, we obtain high-quality crystals of the noncentrosymmetric three-dimensional MOF Zn(3-ptz)2, mixed phases involving the zinc-aqua complex [Zn(H2O)4(3-ptz)2]·4H2O, and two-dimensional MOF crystals Zn(OH)(3-ptz) with a tunable microrod morphology, keeping reaction time, temperature, and metal−ligand molar ratio constant. Structures are characterized by X-ray diffraction, scanning electron microscopy, Fourier transform infrared spectroscopy, and UV−vis spectroscopy. We discuss the observed structural diversity in terms of the relative abundance of hydroxo-zinc species in solution for different values of pH. © 2018 American Chemical Society